Civic virtues dalam pendidikan moral dan kewarganegaraan di Indonesia era orde baru - Samsuri Samsuri (Jurnal Civics: Media Kajian Kewarganegaraan, 2004)
This paper described the role of New Order Regime in Indonesia to build the citizen characters through the educational system. The regime effort to inculcate its interpretation on Pancasila (Five Principles) such as "Pedoman Penghayatan dan Pengamalan Pancasila" (P4). Citizens have been forced to receive and agree what regime intentions on Pancasila. They should be loyal to what regime interests on Pancasila. In the schooling, the New Order Regime has established P4 as core contents of civic virtues to build "good citizen" characters. Some policies in the educational (schooling) system released namely "Pendidikan Moral Pancasila" (Education of Moral Pancasila, PMP) and "Pendidikan Pancasila dan Kewarganegaraan" (Pancasila dan Civic Education, PPKn). This paper seemed the political decision making on how civic virtues have been implemented in the textbooks and two curriculum periods (1984 and 1994). The last, this paper examined the opportunity and prospect the new paradigm of civic education post-1998, i.e. the transitional democracy period after the fall of Suharto as leader profile of the New Order Regime.